Navigating constraints: news values and journalistic role performance in Chinese state media VR news - Zhou, Yongyuan (Frontiers in Communication, 2024)
This study explores the intersection of virtual reality (VR) technology and journalism, with a particular focus on the application of VR in news productions by China Central Television (CCTV). Through a comprehensive content analysis of 234 VR news productions, the research evaluates how immersive elements are utilized, the prevailing news values, and the performance of journalistic roles within these productions. The findings indicate that, while VR enhances audience engagement through immersive experiences, its application in CCTV's VR news remains limited in scope. The technology is primarily employed within traditional journalistic frameworks, often emphasizing the loyal-facilitator role. The study reveals that immersive journalism at CCTV tends to support statealigned narratives, promoting positive news values and limiting the critical engagement typically associated with more interventionist journalistic models. By examining the news values and the nuanced performances of journalistic roles in the context of VR news, this research contributes to the broader understanding of how emerging technologies like VR are shaping journalistic practices in authoritarian media systems, offering insights into both the potential and limitations of VR in enhancing audience engagement while maintaining journalistic integrity.